Pengaruh Pemahaman Peraturan Perpajakan, Modernisasi Sistem Administrasi Perpajakan, dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Zainita Putri Madurano, Sabrina; Umaimah, Umaimah (CV. Lafadz Jaya, 2023)
This study aims to examine the influence of understanding tax regulations, modernizing the tax administration system, and taxpayer awareness of individual taxpayer compliance. This study uses a quantitative approach with a sampling method, namely purposive sampling and samples obtained by 50 respondents. The population in this study is online business actors importing South Korean products in the East Java Region. The data used in this study is primary data in the form of questionnaires. The data analysis technique used is multiple linear regression with the testing tool used is the SPSS Version 16.0 program. The results of this study show that understanding of tax regulations and modernization of the tax administration system have no effect on individual taxpayer compliance, while taxpayer awareness has a positive and significant effect on individual taxpayer compliance.